Synthesis of thiazol derivative compounds from Î±-bromo asil bromida and thiourea - ., Tjiptasurasa (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
Thiazol compounds are mostly used as therapeutics in varies effects. These compounds could be synthesized from starting materials that had been produced by local agrochemical industries i.e. alcohol (from the alcohol factories) and urea (from the fertilizer factory). Yielded bromacylbromide could be used to acylate urea derivatives to form aliphatic bromacylurea. When thiourea was used the cyclization product happened i.e. occurred thiazolon derivatives (without bromine). The lost of bromine could be detected by losing of cluster peak of bromine isotope on MS-spectra. The products of these processes were pure, there were 2-aminothiazol- 4-one 2-amino-5-methyl-thiazol-4-one and 2-amino-5-ethyl-thiazol-4-one. Key word : alcohol, thiourea, aminothiazol-4-one.